2020
DOI: 10.1111/roie.12473
|View full text |Cite
|
Sign up to set email alerts
|

A new impetus for endogenous growth: R&D offshoring via virtual labor mobility

Abstract: We develop a simple North-South model of quality ladders to show that the virtual mobility of labor across time zones, facilitated by the advance in communication technology, can raise the endogenous growth rate of the world economy. The unique balanced growth rate is increasing in the endowments of skilled labor in both countries and decreasing in the rate of impatience. Moreover, we find that partial R&D offshoring to the South has initially a negative effect on the level of skilled wages in the North, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In contrast to the AKtype models by Kikuchi and Marjit (2011) and Marjit and Mandal (2017), which focused on the roles of intermediate business services, Nakanishi and Long (2018) have constructed a Schumpeterian qualityladder model of endogenous growth with two countries (North and South) located in the opposite time zones. 14) They have paid special attention to the roles of outsourcing of research and development (R&D) activities conducted by employing skilled workers.…”
Section: Economic Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the AKtype models by Kikuchi and Marjit (2011) and Marjit and Mandal (2017), which focused on the roles of intermediate business services, Nakanishi and Long (2018) have constructed a Schumpeterian qualityladder model of endogenous growth with two countries (North and South) located in the opposite time zones. 14) They have paid special attention to the roles of outsourcing of research and development (R&D) activities conducted by employing skilled workers.…”
Section: Economic Growthmentioning
confidence: 99%
“…If some steps of an R&D project are outsourced from North to South (i.e., R&D offshoring) during the nighttime of North by taking advantage of time zone difference, the total number of R&D projects that can be completed in a year will be doubled. With this setting, Nakanishi and Long (2018) have shown that the R&D offshoring brings about an immediate decrease in the Northern skilled wage rate, an immediate increase in the Northern unskilled wage rate, and an increase in the longrun growth rate along the balanced growth path. In their model, the increased access to the pool of Southern skilled workers due to the virtual labor mobility via communications network is the driving force of economic growth.…”
Section: Economic Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Mandal (2015) also deduce the possibility of growth through an increase in capital accumulation in an extended model of Kikuchi and Marjit (2011). There is another interesting paper, [Marjit and Mandal (2017)] which delineates why trade across TZ helps to attain a “higher steady-state growth.” Nakanishi and Long (2020), the latest one so far also observes that trading labor services across TZ increases the endogenous growth rate. There has also been research on how virtual trade across TZ affects factor prices and their demand, along with changes in output.…”
Section: Introductionmentioning
confidence: 97%
“…Following this work, Kikuchi and Marjit (2011) and Marjit and Mandal (2017) analyze how trade across time zones can lead to automatic increase in the growth rate. Nakanishi and Van Long (2020) discuss virtual mobility of labor and wage inequality in models with separated time zones and finally in a recent book Marjit, Mandal and Nakanishi (2020) discuss various aspects of trade due to separated time zones.…”
Section: Introductionmentioning
confidence: 99%